Exploring solutions to the muon g-2 anomaly in a 3-3-1 model under flavor constraints - A. Doff; João Paulo Pinheiro; C. A. de S. Pires (European Physical Journal C: Particles and Fields)
Abstract The magnetic moment of the muon can receive significant two-loop contributions from a light pseudoscalar. Notably, the spectrum of scalars of 3-3-1 models includes one pseudoscalar. However, this scalar spectrum inevitably gives rise to flavor-changing neutral current (FCNC) processes. In this study, we examine, within the 3-3-1 model with right-handed neutrinos, whether such spectrum of scalars can account for the anomalous magnetic moment of the muon, considering the constraints imposed by B-meson decays, meson mixing, and invisible Higgs decays. Our principal finding reveals that a pseudoscalar with mass around 66 GeV and $$\tan β =58$$ tan β = 58 can account for the $$g-2$$ g - 2 anomaly without conflicting with flavor physics.